Communication technology changes and challenges - Shukla, Rajiv (New Delhi Rajat, 2000)
Communication technology is the science of techniques of communication which utilizes the most efficient principles and practices of newer techniques in a systematic way.The modern communication opportunities and challenges has opened new vistas in commun
Keywords: Communication and technology; Technology; Massmedia-Laws and legislation; Communication